MATHEW, K. S. (2017), Shipbuilding, Navigation and the Portuguese in Pre-Modern India, New Delhi, Manobar. ISBN 978-93-5098-157-3, 222p. - Oliveira, Liliana (História: revista da Faculdade de Letras da Universidade do Porto, 2021)
–